Study of Responsive Environment Aspects Within The Scope of Cultural Heritage Areas: Analysis of Kotabaru Boulevard in Yogyakarta - Jessica Fitriani Putri; Rony Gunawan Sunaryo; Trias Mahendarto (Journal of Architectural Design and Urbanism, 2026)
The Kotabaru area of Yogyakarta is a cultural heritage site with a colonial garden city character that can still be seen in its grid pattern, boulevards, monumental vegetation, and Indis-style buildings. This study examines the quality of the responsive environment in the Kotabaru boulevard corridor, specifically Jalan Suroto, using the theoretical framework of Bentley, Lynch, Southworthand Shirvani. The method used is descriptive-qualitative through in-depth observation, documentation, and interpretation of the theory of spatial responsiveness. The results of the study show that the corridor has high potential in terms of legibility, variety, richness, and vitality, but is still low in terms of robustness, pedestrian ways, visual appropriateness, and justice. The change in building function from colonial residences to modern commercial buildings increases vitality but weakens visual control and public space quality. Disconnected sidewalks, parking above pedestrian areas, uncontrolled signage, and changes to building facades are the main challenges in fulfilling the principles of a responsive environment in cultural heritage areas. This study produced a theoretical approach to strengthening the quality of heritage corridors by considering urban conservation, modern visual restrictions, and the improvement of pedestrian space.